Study on the measurement of China’s monetary policy uncertainty and its macroeconomic effects - Kewei, Zhang; Wenfu, Wang (Transformations In Business & Economics, 2025)
Based on data from the Financial Times, this paper constructs a monthly index of China’s monetary policy uncertainty from 2000 to 2023. Using a Time-Varying Parameter Structural Vector Autoregression (TVP-SV-VAR) model, the study examines the effects of monetary policy uncertainty on macroeconomic variables in a phased manner. First, monetary policy uncertainty negatively impacts the growth rate of economic levels. Second, it has been observed that the effect of monetary policy uncertainty on the inflation rate exhibits an inverted U-shape. The impact of monetary policy uncertainty on the macroeconomy varies significantly across economic cycles. During economic upswings, increased monetary policy uncertainty drives inflation rates higher. However, during periods of economic stability and downturns, the impact of monetary policy uncertainty on inflation rates is negative. Finally, it has been also found that monetary policy uncertainty positively impacts both interest rates and exchange rates. This study reconstructs the index of China’s monetary policy uncertainty and provides a reference for further research on the macroeconomic impacts of monetary policy uncertainty.